Design And Build Of Gabah Processing Machine 5 Kg Capacity Transmission System - Anggoro Dwi Koencoro; Hesti Istiqlaliyah (Universitas Muhammadiyah Sidoarjo, 2021)
Grain processing machinesis a machine designed to improve map welfareni in the district area Nganjuk. This engine component containsri of the paring system,separator system,transmission systemand order. The transmission part serves totransmits the rotation of the drive motor to the driven mechanism through the pully and v-belt. This machine has a capacity of 5 kg at a time.The discussion focused on the transmission system and frame. Main powerin the form of an electric motorto be transmittedusing pulleys and V-belt. Using motor 0.75HP with a motor rotation of 1400 rpm on the main motor. Transmi typesi used pulleys and belts-v, with belt type A. The drive pulley on the motor is 75mm,puli on a 75mm grinder.